Pair bonds, reproductive success, and rise of alternate mating strategies in a social carnivore. (7th August 2019) - Ausband, David E
Abstract: Monogamy is commonly observed across a wide variety of species and taxa and arises when young are altricial, parental investment in young is high, and mate monopolization is generally not possible. In such species, pairs may bond for multiple breeding seasons while successfully rearing young. Individuals, however, may attempt to bypass the dominant mating strategy particularly when breeding opportunities are limited. Currently, we do not know how pair bond duration affects the efficacy of alternative mating strategies in populations with a monogamous mating system. Additionally, inferences about pair bond effects on reproductive success (i.e., both clutch size and recruitment) are largely limited to long-lived birds and little is known about effects on mammalian cooperative breeders. I used genetic sampling and pedigrees to examine the effects of pair bond duration on reproductive success (i.e., litter size, recruitment) and mating strategies in a population of gray wolves ( Canis lupus ) in Idaho, USA. There was a positive, marginally significant relationship between pair bond duration and apparent survival of offspring. Increased pair bond duration was also associated with a dampening in the prevalence of other alternative mating strategies such as sneaker males and polygamy. The selective advantage of alternative mating strategies is a combination of population, group (for applicable species), individual, and social influences such as pair bonds. The distribution of pair bonds in a monogamous population affects the selective advantage, and hence frequency, of various mating strategies observed. Abstract : Many species are monogamous and long-lived. We have a poor understanding of how breeding pair bonds affect reproductive success and the prevalence of alternative mating strategies in species that live and breed in groups. I found that the longer the pairs were together, the better their young survived. Additionally, pairs bonded longer were less likely to include sneaker males or polygynous matings in their groups.